Novel Method of Detecting Moving Object in Video. (2016) - Risha, K.P.; Kumar, A. Chempak
Abstract: In the modern trends, intelligent video surveillance system is a very important and relevant topic of research. It is well suited for a broad range of applications which includes, video communication, security and surveillance, public areas such as airports, traffic control, monitoring activities at traffic intersections for detecting congestions, and then predicting the traffic flow which assists in regulating traffic, underground stations, mass events, etc. The main disadvantage of the system is, the storage space required for storing these data and retrieval of the same on demand. For these human resources are needed but manually reviewing the large amount of data often impractical. The proposed work focused on bringing effective and efficient system with intelligence to avoid human intervention in identifying security threats. In this paper, the moving objects in a video detected by using a method of optic flow with morphological operation.